2019
DOI: 10.1029/2019gc008277
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Geodynamic Modeling in the Southeast Carpathians: Upper Mantle Flow‐Induced Surface Topography Anomalies

Abstract: Spectral variations of gravity and topography data show nonisostatic compensation of elevation in the Southeast Carpathians that is consistent with our new residual topography calculations. Multidimensional thermomechanical models are created to consider a possible mantle flow component of the surface topography with varying temperature models and crustal configurations. The temperature anomalies derived from large‐scale P wave velocity anomalies and combined temperature model are estimated as input for the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 92 publications
0
17
0
1
Order By: Relevance
“…Ren et al, 2012;Borleanu et al, 2017). The upwelling hypothesis (Gögüş et al, 2016;Maţenco, 2017;Şengül Uluocak et al, 2019) is also supported by the occurrence of post-collisional volcanism (Seghedi et al, 2011), and the observed high heat flux values (up to mW/m 2 locally, Demetrescu and Veliciu, 1991). A reduction in dt can alternatively be explained by the presence of melt and/or water, which can drastically alter mantle velocities and LPO behaviour (Karato and Jung, 1998;Katayama et al, 2004), by promoting the transition from dislocation creep to diffusion creep, which prevents the formation of a preferred mineral orientation (e.g.…”
Section: Asthenospheric Upwelling In the Transylvanian Intra-arc Basinmentioning
confidence: 99%
“…Ren et al, 2012;Borleanu et al, 2017). The upwelling hypothesis (Gögüş et al, 2016;Maţenco, 2017;Şengül Uluocak et al, 2019) is also supported by the occurrence of post-collisional volcanism (Seghedi et al, 2011), and the observed high heat flux values (up to mW/m 2 locally, Demetrescu and Veliciu, 1991). A reduction in dt can alternatively be explained by the presence of melt and/or water, which can drastically alter mantle velocities and LPO behaviour (Karato and Jung, 1998;Katayama et al, 2004), by promoting the transition from dislocation creep to diffusion creep, which prevents the formation of a preferred mineral orientation (e.g.…”
Section: Asthenospheric Upwelling In the Transylvanian Intra-arc Basinmentioning
confidence: 99%
“…This delamination-style progressive removal of the lithosphere and associated mantle dynamics suggest a distinct transient migratory pattern of surface subsidence and uplift and magmatism as well as crustal shortening and extension, different from the stationary convective removal process (Houseman et al, 1981;Molnar et al, 1993;Elkins-Tanton, 2007;Göğüş & Pysklywec, 2008b;Wang & Currie, 2015;Göğüş, Pysklywec, Şengör, et al, 2017;Bodur et al, 2018). Such processes of migrating instability mechanism with the surface subsidence and uplift have been linked with various regions: the Colorado Plateau (Bird, 1979;Levander et al, 2011), the Southern Sierra Nevada (Le Pourhiet et al, 2006;Saleeby et al, 2012Saleeby et al, , 2013, Wallowa mountains-Columbia basalts (Camp & Hanan, 2008;Darold & Humphreys, 2013), Andes , Southeast Carpathians (Girbacea & Frisch, 1998;Fillerup et al, 2010;Göğüş et al, 2016;van Wyk de Vries et al, 2018;Şengül Uluocak et al, 2019), Apennines (Channell & Mareschal, 1989;Chiarabba & Chiodini, 2013), Alboran Domain-western Mediterranean (Baratin et al, 2016;Docherty & Banda, 1995;Valera et al, 2008), Eastern Anatolia (Keskin, 2003;Şengör et al, 2003, 2008Göğüş & Pysklywec, 2008a;Göğüş et al, 2011), North Island of New Zealand (Stern et al, 2013), Pamir Mountains (Chapman et al, 2017), and Rhodope-Balkans (Burg, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A mix of the two end member ideas is the trap‐door delamination hypothesis (Fillerup et al, 2010; Gîrbacea & Frisch, 1998) in which a continental lithospheric fragment possibly containing eclogitic lower crust, initially flat under Transylvania, underwent delamination sensu Bird (1979). It has become clearer in recent years that the thickness of the Vrancea slab (>100 km and possibly over 150 km) makes it most likely a fragment of the foreland continental lithosphere subducted under the Carpathians (Şengül‐Uluocak et al, 2019), while any leading oceanic fragment is not detectable today in the geophysical data. Therefore, whenever we refer to the “Vrancea slab” in this paper, we envision a piece of continental lithosphere containing a sizable portion of crust being subducted and undergoing ultrahigh pressure metamorphism, similar to the Pamirs (Ducea et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The Vrancea slab is arguably the best continental example of active vertical tectonics in which a lithospheric piece is unquestionably descending into the asthenospheric mantle. The entire region is characterized by relatively thin crust, and topography is in part dynamically supported from the uppermost mantle (Şengül‐Uluocak et al, 2019).…”
Section: Introductionmentioning
confidence: 99%